Identification of β-glucosidase 1 as a biomarker and its high expression in hepatocellular carcinoma is associated with resistance to chemotherapy drugs. (2nd April 2016) - Zhang, Ye; Zhu, Kuiyu; Miao, Xiaofei; Hu, Xingqian; Wang, Tong
Abstract: Context and objective : Long-term prognosis of hepatocellular carcinoma (HCC) patients is challenging, and novel biomarkers are needed to predict patient risk and serve as potential therapeutic target. Results : We found β-glucosidase 1 is significantly overexpressed and activated in primary HCC tissue and multiple HCC cell lines. β-Glucosidase 1 expression is associated with predicting prognosis of HCC patients under chemotherapy. Silencing β-glucosidase 1 inhibits growth and survival of HCC cells, with preferential inhibitory effects on high β-glucosidase 1-expressing cells. Combination of chemo drug with β-glucosidase 1 inhibitor sensitized HCC cells to chemotherapy. Conclusion : Our data support β-glucosidase 1 as a HCC biomarker due to its prognosis significance.